Approach for Scenario-Based Test Specifications for Virtual Commissioning - Schneider, Marcel; Gausemeier, Jürgen; Schmuedderich, Tanja; Trächtler, Ansgar (Proceedings of the DESIGN 2014 - 13th INTERNATIONAL DESIGN CONFERENCE)

Towards a Production System Specification Technique for Functionally Graded Components - Petersen, Marcus; Bauer, Frank; Hess, Stefan; Gausemeier, Jürgen; Gräßler, Iris (Proceedings of the DESIGN 2014 - 13th International DESIGN Conference | Volume 2)
Functional gradation means a tailored distribution of properties over the spatial dimensions of a component based on a complex manufacturing process chain. The synthetisation of these processes requires a framework that generates numerous information for the production system elaboration during the further design phases. Therefore a production system specification technique for functionally graded components is presented. The specification technique enables the visualisation of the resulting process chain with all information in a descriptive manner and offers an interface for Microsoft Visio.

Towards a Production System Specification Technique for Functionally Graded Components - Petersen, Marcus; Bauer, Frank; Hess, Stefan; Gausemeier, Jürgen; Gräßler, Iris (Proceedings of the DESIGN 2014 - 13th International DESIGN Conference)
Functional gradation means a tailored distribution of properties over the spatial dimensions of a component based on a complex manufacturing process chain. The synthetisation of these processes requires a framework that generates numerous information for the production system elaboration during the further design phases. Therefore a production system specification technique for functionally graded components is presented. The specification technique enables the visualisation of the resulting process chain with all information in a descriptive manner and offers an interface for Microsoft Visio.